Impediments to Practice in Contemporary Paganism - Reece, Gwendolyn (Pomegranate, 2015)
This quantitative study is based on data from a large-scale national survey of Pagans, Witches, and Heathens in the United States (N=3,318) that was conducted by the author and examines the prevalence and severity of impediments to practice encountered by American Pagans. Obstacles can be organized into the following categories: (1) those rooted in interactions with the dominant culture in which Pagans live; (2) challenges arising from the non-institutional nature of Paganism; (3) requirements related to the practice of magick; (4) demands stemming from educational/developmental trajectories; and (5) pragmatic challenges encountered when trying to live according to one’s values. Contemporary Paganism is in the early stages of routinization. The analysis reveals that the “house church,” volunteer clergy model poses real, pervasive challenges not only for Paganism in general, but for the leaders and clergy in particular. The importance of nature is a notable feature of Paganism and the most common obstacle to religious practice discovered is the expense of living a Green lifestyle. Fear of prejudice and conflicts with the values embedded within the dominant culture’s educational system are also prevalent barriers that affect practice.